The relationship between work period and hearing disorder caused by noise in workers of PT. Kayu Perkasa Raya - Astin prima sari; Rakhma Auliya Sari; Ika Dyah; Wahju Budi Martono (Universitas Muhammadiyah Surabaya, 2024)
Noise Induced Hearing Loss (NIHL) is sensorineural deafness caused by hearing threshold values in the workplace. According to the Regulation of the Minister of Manpower and Transmigration Number 13 of 2011 it regulates the threshold and chemical factors. The threshold value is 85 dB with 8 hours/day noise exposure time. This study aimed to determine the relationship between work period and the incidence of NIHL in PT. Kayu Perkasa Raya. The type of research used was quantitative with observational analytic methods. Data was obtained from questionnaires and audiometric results. The research design used cross-sectional, a study between measurement and observation variables that were carried out simultaneously. The sampling technique was purposive sampling. The analysis used using chi-square. The distribution was based on a working period. During the working period of ≥ 5 years, there were 10 people (33.3%) who experienced NIHL, and 20 people (66.7%) who did not experience NIHL. During the working period < 5 years, two people (11.1%) experienced NIHL, and 16 people (88.9%) did not experience NIHL (p=0.081). In conclusion, no significant relationship exists between the work period and NIHL at PT.Kayu Perkasa Raya.